Aldehyde Substituted Phthalocyanines: Synthesis, Characterization and Investigation of Photophysical and Photochemical Properties - Sen, Pinar; Yildiz, S. Zeki; Erdogmus, Ali; Dege, Necmi; Atalay, Yusuf (SPRINGER/PLENUM PUBLISHERS, 2016)
The new free and nickel phthalocyanine derivatives, tetrakis [(2-formylphenoxy)-phthalocyanine (4), tetrakis [(2-formylphenoxy)-phthalocyaninato]nickel(II) (5) have been synthesized via de-protection of tetra acetal-substituted phthalocyanines in acetic acid/FeCl3 system. The starting phthalocyanines, tetrakis [(2-(1,3-dioxolan-2-yl)phenoxy)-phthalocyanine (2) and tetrakis [(2-(1,3-dioxolan-2-yl)phenoxy)-phthalocyaninato]nickel (3), were prepared by the tetramerization of 4-(2-(1,3-dioxolan-2-yl) phenoxy) phthalonitrile (1). The new compounds have been characterized by the combination of FT-IR, H-1 NMR, UV-Vis, Mass spectra and elemental analysis. Compound 1 crystallizes in the Orthorhombic, space group Pbca with a = 9.2542 (4) , b = 13.3299 (5) , c = 23.2333 (11) , and Z = 8. Compound 1 is built up from two planar groups (phthalonitrile and phenoxy), with a dihedral angle of 69.693(36)A degrees between them and non-planar dioxolane group. We report a combined experimental and theoretical study on molecule 1, as well. Geometric, spectroscopic and electronic properties of compound 1 has been calculated using B3LYP method and 6-311++G(dp) basis set. Fluorescence spectroscopy was applied to record the photoluminescence spectra of the prepared phthalocyanines and the photophysical and photochemical properties were examined in DMSO.
Keywords: Synthesis; Single crystal; X-ray structure; Theoretical calculation; Phthalocyanine; Fluorescence property; Singlet oxygen; Photodegradation; ZINC PHTHALOCYANINES; MOLECULAR-STRUCTURE; AGGREGATION; METALLOPHTHALOCYANINES; Biochemistry & Molecular Biology; Chemistry